2013
DOI: 10.1039/c3cp51061a
|View full text |Cite
|
Sign up to set email alerts
|

Assemblies of polyvinylpyrrolidone-capped tetrahedral and spherical Pt nanoparticles in polyelectrolytes: hydrogen underpotential deposition and electrochemical characterization

Abstract: Polyvinylpyrrolidone (PVP)-capped Pt nanoparticles (NPs) were synthesized in mostly tetrahedral (TH-Pt, [edge] = 4.3 ± 0.7 nm) or spherical (S-Pt, [d] = 3.4 ± 0.8 nm) shapes and assembled layer-by-layer in poly(diallyldimethylammonium) chloride on electrodes driven by electrostatic and hydrophobic interactions. The nanostructured Pt electrodes were characterized using hydrogen underpotential deposition (H(upd)) in 1 M H2SO4. The H(upd) charge increased linearly with the PDDA-Pt NP adsorption cycle measured up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 66 publications
(129 reference statements)
0
2
0
Order By: Relevance
“…Platinum nanoparticles with a capping of non-electroactive cationic polyelectrolyte, such as polydiallyldimethyl ammonium chloride (PDDA) assembled into layer-by-layer arrays have been successfully employed in electrocatalysis of oxygen reduction reactions and hydrogen evolution under potential deposition [9]. Furthermore, platinum nanoparticles capped using polyvinylpyrrolidone (PVP) and assembled in LBL arrays showed an enhancement of formic acid and methanol oxidation reactions [10].…”
Section: Introductionmentioning
confidence: 99%
“…Platinum nanoparticles with a capping of non-electroactive cationic polyelectrolyte, such as polydiallyldimethyl ammonium chloride (PDDA) assembled into layer-by-layer arrays have been successfully employed in electrocatalysis of oxygen reduction reactions and hydrogen evolution under potential deposition [9]. Furthermore, platinum nanoparticles capped using polyvinylpyrrolidone (PVP) and assembled in LBL arrays showed an enhancement of formic acid and methanol oxidation reactions [10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the -0.05V oxidation current peak appears to increase [69]. As reported by Jaber et al, who performed potential scans reaching into the Pt-oxide region, the H(W) peak increase, without potential shifting, should rather be attributed to structural polymer rearrangement, enhancing the accessibility of burried hydrogen adsorption sites on PVP-capped Pt NPs [48]. The same authors concluded that (100) sites remain PVP-free, so that reactions of H(S) are undisturbed by capping.…”
Section: Cyclic Voltametrymentioning
confidence: 55%